Application of Defoliated Chrysanthemum Leaves and Combination of Organic Fertilizer to the Yield and Quality of Chrysanthemum Flowers - A.A. Sagung Putri Risa Andriani; I Gusti Made Arjana; I Gusti Ayu Dewi Seri Rejeki (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The market value of horticultural products, particularly ornamental plants, is quite high. It is necessary to conduct research on the introduction of appropriate technology for increasing the intensity of chrysanthemum cultivation, such as the use of chrysanthemum leaf messenger and a combination of manure, which is formulated with local resources in chrysanthemum flowers to improve quality and add value and utilize the potential of agricultural resources that are easy to apply based on the capacity of farmers and have a real impact on increasing income. This study's objective was to determine the optimal concentration of chrysanthemum leaves and the optimal combination of manure for enhancing the production and quality of chrysanthemums. Using a Factorial Randomized Block Design, field research is conducted in a greenhouse using two factors: the dosage of defoliated chrysanthemum leaves and a mixture of manure. The obtained data were statistically analyzed using the ANOVA test. If the effect of a single treatment is genuine or very real, the average value test is continued. Least significant difference (LSD) is 5%, whereas Duncan's 5% indicates an interaction between the two factors tested. The treatment of defoliated leaves had a real to very real effect on all variables, with the exception of stem diameter, whereas the combination treatment of organic fertilizers had a real to very real effect on all variables. The interaction between the quantity of defoliated leaves and the combination of organic fertilizer has no significant effect on all variables. The administration of a dose of 5 tons/ha and the combined use of goat manure and pig manure increased the length of the flower stalk, the weight of the flower stalk, the diameter of the stem, the diameter of the flower, the fresh weight of the most cost-effective flowers, and the proportion of leaves infected with rust. According to SNI 01-4478-88, the chrysanthemums produced in this investigation are of quality class A.